2013
DOI: 10.1002/pen.23675
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous first normal stress difference behavior of polymer nanocomposites and liquid crystalline polymer composites

Abstract: The first normal stress difference (N1) behavior of polymer nanocomposites and liquid crystalline polymer (LCP) composites is a measure of elasticity and is affected by shear stress as a result of morphological alterations at the molecular and nanostructure levels. In this study, the steady shear rheological behaviors of polylactide (PLA) and nanographite platelet (NGP) bionanocomposites containing 1, 2, 3, and 5 wt% nanofiller were investigated. The shear rheological properties of glass fiber‐filled LCPs (fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 77 publications
1
12
0
Order By: Relevance
“…31,33,53 Majority of these systems constitute of very stiff building blocks (rod like materials), for example, semidilute non-Brownian carbon nanotube suspensions. 33 The origin of negative normal stress for these system is not precisely known but different theories have been proposed including tumbling of rod-like molecules and contraction of a sheared sample due to the alignment of rod like stiff molecules.…”
Section: Negative Normal Stressmentioning
confidence: 99%
“…31,33,53 Majority of these systems constitute of very stiff building blocks (rod like materials), for example, semidilute non-Brownian carbon nanotube suspensions. 33 The origin of negative normal stress for these system is not precisely known but different theories have been proposed including tumbling of rod-like molecules and contraction of a sheared sample due to the alignment of rod like stiff molecules.…”
Section: Negative Normal Stressmentioning
confidence: 99%
“…The authors have already reported the morphological, thermal, mechanical and shear rheological characterizations of the samples . Figure illustrates the transmission electron microscopy (TEM) of PLA/NGP composites of this study, which were comprehensively investigated and reported elsewhere .…”
Section: Introductionmentioning
confidence: 85%
“…The authors have already reported the morphological, thermal, mechanical and shear rheological characterizations of the samples. [19,[41][42][43][44] Figure 1 illustrates the transmission electron microscopy (TEM) of PLA/NGP composites of this study, which were comprehensively investigated and reported elsewhere. [19] The morphological evaluation of the samples through TEM and X-ray diffractometer (XRD) analysis were indicative of the dominance of intercalation in coexistence with agglomeration and negligible platelet individualization of NGP fillers within the PLA matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, in the case of unfilled LCPs the value of N 1 remained positive (Fig. 4.7) Narimissa et al 2013).…”
Section: First Normal Stress Differencementioning
confidence: 93%